Learning Loss Mitigation: The Perspectives of Senior High School English Teachers in Indonesia - Hildianti, Diana; Rahayu, Puji (Universitas Muhammadiyah Mataram, 2024)
Teachers play a critical role in addressing the learning loss due to the Covid-19 school disruption by creating various strategies to overcome the loss. This paper aims to investigate several factors which impact to student’s performance and teachers’ efforts in overcoming the learning loss during Covid-19 pandemic. In a qualitative method with an open-ended survey and interview, 35 high school English teachers with at least 3 years of experience shared their experiences to overcome the learning loss. 10 teachers are clarifying their strategies to cope with learning loss due to Covid-19 school disruption by inadeptly interviewed. The thematic analysis of the data found that the teachers' strategies to overcome learning loss, teacher-student interaction, curriculum adaptation, and support from the government and school [1]. Most of the English teachers perceived that learning loss happened due to the lack of teacher-student interaction, inadequate facilities, and inauthentic writing skills during the Covid-19 pandemic. To overcome this, teachers adapted English modules with media technology to simplify English lessons and build learning independence despite the incomprehensive lessons. The support from the government and school-ICT training, technology teaching tools, internet, and E-learning sources - helps teachers reduce the learning loss possibility. The findings indicated the importance of supportive and adaptive English teachers in mitigating learning loss due to Covid-19 school disruption.